New data on Cladocera (Crustacea: Branchiopoda) of Sabah State, Borneo Island, Malaysia - Sinev, Artem Y.; Yusoff, Fatimah M. (Zootaxa, 2018)
Unlike those in the mainland of Southeast Asia, the Cladocera of the Malay Archipelago has not been intensively studied, except for the state of Sabah in the north-eastern part of the Borneo island. This study aimed to complete the inventory of the Cladocera in Sabah by looking at different types of water bodies including oxbow lakes, small lakes, reservoirs, ponds, ditches and paddy fields. From 32 sites examined, 35 species of cladocerans, nine of which were new records to Sabah, were found from 25 localities. With this new finding, the total number of cladoceran species in Sabah increased to 39 species, including five species of Sididae, four species of Daphniidae, one species of Moinidae, five species of Macrothricidae, two species of Ilyocryptidae, and 22 species of Chydoridae. Only 8 % ( three species) of Sabah cladocerans are true planktonic. This study illustrated that most cladocerans were associated with substrates in the littoral zone and thus appropriate sampling methods should be employed in different microhabitats for comprehensive biodiversity assessment.